p73 as a Tissue Architect - Maeso-Alonso, Laura; López-Ferreras, Lorena; Marques, Margarita M.; Marin, Maria C. (Frontiers in Cell and Developmental Biology, 2021)
The TP73 gene belongs to the p53 family comprised by p53, p63 and p73. In response to physiological and pathological signals these transcription factors regulate multiple molecular pathways which merge in an ensemble of interconnected networks, in which the control of cell proliferation and cell death occupies a prominent position. However, the complex phenotype of the Trp73 deficient mice has revealed that the biological relevance of this gene does not exclusively rely on its growth suppression effects, but it is also intertwined with other fundamental roles governing different aspects of tissue physiology. p73 function is essential for the organization and homeostasis of different complex microenvironments, like the neurogenic niche, which supports the neural progenitor cells and the ependyma, the male and female reproductive organs, the respiratory epithelium or the vascular network. We propose that all these, apparently unrelated, developmental roles, have a common denominator: p73 function as a tissue architect. Tissue architecture is defined by the nature and the integrity of its cellular and extracellular compartments, and it is based on proper adhesive cell-cell and cell-extracellular matrix interactions as well as the establishment of cellular polarity. In this work, we will review the current understanding of p73 role as a neurogenic niche architect through the regulation of cell adhesion, cytoskeleton dynamics and Planar Cell Polarity, and give a general overview of TAp73 as a hub modulator of these functions, whose alteration could impinge in many of the Trp73-/- phenotypes.